Psychological and Pedagogical Conditions of Motivating Students’ Educational Activity - Bakatanova, V.; Potjomkina, К. (Problems of Engineer-Pedagogical Education, 2019)
In the course of the study, a survey was conducted among the students of Ukrainian Engineering Pedagogics Academy with the aim of identifying the level of their external and internal motivation, the level of development of their internal motivation, the main incentives and ways of their motivation to study, as well as factors that reduce the level of motivation of students in the educational process. The authors’ questionnaire about students’ motivation was aimed at identifying the motives and incentives to study and to get higher education, as well as at identifying the reasons that suppress the motivation to study according to the selected specialty. On the basis of the analysis of the results of the survey, factors influencing students’ motivation and psychological and pedagogical conditions of motivating their learning activities have been revealed. Certain psychological and pedagogical conditions are based on the concept of the pedagogical system and contain the following: awareness of all the departments of a higher educational institution of a common goal, which is to form a professional focus on engineering and pedagogical activity within the framework of the specialty chosen by students; selection of advanced teaching and learning content which meets requirements of the labor market; use of innovative methods of pedagogical communication; competent higher education teaching professionals with great skills in managing students’ motivation; requirements for students, their values, professional interests, abilities, level of development of their professional focus, level of general education, general cultural level, – which should necessarily be taken into account during the competitive selection of students for training. To overcome the existing organizational, substantive, material and personnel problems in the process of engineering and pedagogical training, the authors put forward recommendations concerning the implementation of the identified psychological and pedagogical conditions for motivating students' academic activities.